2010
DOI: 10.4137/bmi.s5522
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mRNA and microRNA Stabilization in Peripheral Human Blood for Multicenter Studies and Biobanks

Abstract: In this study we evaluate the suitability of two methods of RNA conservation in blood samples, PAXgene and RNAlater, in combination with variable shipping conditions for their application in multicenter studies and biobanking. RNA yield, integrity, and purity as well as levels of selected mRNA and microRNA species were analyzed in peripheral human blood samples stabilized by PAXgene or RNAlater and shipped on dry ice or at ambient temperatures from the study centers to the central analysis laboratory. Both exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…If high-quality DNA is needed or the target is RNA, samples should be kept frozen at low temperature (see Akor-Dewu et al, 2014;Head et al, 2014) or preserved in RNAlater (e.g. Weber et al, 2010), FTA® cards (e.g. Mendoza et al, 2012) or PAX gene blood tubes until analysis (e.g.…”
Section: Wbcmentioning
confidence: 99%
“…If high-quality DNA is needed or the target is RNA, samples should be kept frozen at low temperature (see Akor-Dewu et al, 2014;Head et al, 2014) or preserved in RNAlater (e.g. Weber et al, 2010), FTA® cards (e.g. Mendoza et al, 2012) or PAX gene blood tubes until analysis (e.g.…”
Section: Wbcmentioning
confidence: 99%
“…RNAlaterÔ (Protocol C) is an aqueous, nontoxic tissue storage reagent that can stabilize and protect cellular RNA in situ in unfrozen specimens, and can also be used for the processing and preservation of white blood cells, including short-term storage or transportation at room temperature and long-term preservation at -80°C. 13 The PAXgene Blood RNA tube (Protocol F) is a kind of blood collection tube that could stabilize intracellular RNA immediately upon blood collection. Some researchers choose to freeze the blood specimen directly at -80°C (Protocol E) without any additives such stabilizers, to rule out the possibilities of toxicity during long-term storage and interference with other possible future assays.…”
Section: Discussionmentioning
confidence: 99%
“…In general, miRNA species are much more stable than mRNA and most studies have not used these methods. Several studies have demonstrated successful isolation and quantitation of specific miRNAs or whole miRNomes from whole blood [42][43][44][45] or tissue [46]. However, few studies have systematically compared RNA stabilization media with a control method.…”
Section: Rna Preservation Reagentsmentioning
confidence: 99%
“…One study directly compared Tempus and PAXgene whole blood stabilization systems and identified small differences in miR30b quantitation [43]. Another detected variation in miRNA quantitation isolated from whole blood preserved in either RNAlater or PAXgene, but noted both systems were appropriate for miRNA analysis [45]. A different study of the PAXgene Tissue stabilization system identified high-concordance in miRNA quantitation between frozen and stabilized specimens (R 2 = 0.95) and reduced concordance between stabilized and formalin-fixed, paraffin embedded (FFPE) tissues (R 2 = 0.81).…”
Section: Rna Preservation Reagentsmentioning
confidence: 99%